In-kind credit provision through contract farming and formal credit markets - Anette Ruml; Martin C. Parlasca (Agribusiness, 2021)
Access to credit is a key prerequisite for the development of smallholder agriculture. However, rural credit markets are typically characterized by market failures and smallholder credit access is limited. Resource-providing contracts are an institutional tool to overcome credit market failures through the provision of production inputs in the form of in-kind credit. Previous research has shown that interlinkage of contract and credit helps farmers overcome financial constraints, foster production investments, and hence increase productivities and income. However, if and how such contract schemes affect farmers' overall demand for and access to formal credit from other sources is not yet well understood. In this article, we therefore investigate the associations of the provision of in-kind credit and farming households' formal credit demand and ability to receive formal credit. We use data of 463 oil palm producers in Ghana and show that participation in contract farming is associated with an increase in credit demand. Concerning credit approval, we find that the outstanding debt of the in-kind credit scheme is associated with a substantially lower likelihood of credit acceptance. However, the results also suggest that farmers can fully compensate this negative effect by informing the bank about the contract, and thus the source of the debt. This indicates that debt acquired from resource-providing contract schemes does not necessarily pose an additional credit constraint to farmers. [EconLit Citation G21, G23, O16, O17].
Keywords: 630; contract farming; credit constraints; Ghana; inkind credits; oil palm